Incremental benefit of late gadolinium cardiac magnetic resonance imaging for risk stratification in patients with hypertrophic cardiomyopathy - Dösch, Christina; Tueluemen, Erol; Akın, Ibrahim; Rudic, Boris; Kuschyk, Jürgen; El-Battrawy, Ibrahim; Becher, Tobias; Budjan, Johannes; Smakic, Arman; Schönberg, Stefan; Borggrefe, Martin; Papavassiliu, Theano (Scientific reports, 2017)
Hypertrophic cardiomyopathy (HCM) has a low risk for sudden cardiac death (SCD). The ESC clinical risk prediction model estimates the risk of SCD using clinical and echocardiographical parameters without taking into account cardiac magnetic resonance (CMR) parameters. Therefore, we compared the CMR characteristics of 149 patients with low, intermediate and high ESC risk scores. In these patients left and right ventricular ejection fraction and volumes were comparable. Patients with a high ESC risk score revealed a significantly higher extent of late gadolinium enhancement (LGE) compared to patients with intermediate or a low risk scores. During follow-up of 4 years an extent of LGE ≥20% identified patients at a higher risk for major adverse cardiac arrhythmic events in the low and intermediate ESC risk group whereas an extent of LGE <20% was associated with a low risk of major adverse cardiac arrhythmic events despite a high ESC risk score ≥6%. Hence, we hypothesize that the extent of fibrosis might be an additional risk marker.